Separation Theorems in Hilbert Spaces as Bases of Convex Programming - Ferreira, M. A. M. (EasyChair Preprint Nº 7884, 2025)
Separation theorems are the bases of convex programming. They are important consequences of Hahn-Banach theorem. This work begins considering vector spaces in broad sense. Then normed spaces and finally Hilbert spaces. It ends with the consideration of these results in convex programming, an important quantitative tool in operations research, finance, management and economics.